HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN PENCEGAHAN PENULARAN TB PARU - Yenni, Yenni; Meliyantari, Resti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The problem of tuberculosis (TB) is a problem that has long been faced by various countries in the world, including Indonesia. Indonesia is ranked third in the world and this requires attention from all parties, because it causes a high burden of morbidity and mortality. Indonesia is one of the countries with the largest tuberculosis burden among 8 countries, namely in third place after India and China and there has been an increase in cases in Indonesia and also in Jambi Province. This study aims to determine the relationship between knowledge and attitudes and measures to prevent transmissions of pulmonary tuberculosis carried out in July 2023 in the working area of the Kemantan Community Health Center, Kerinci Regency. The Research population was families of pulmonary TB sufferers taken with a total sampling of 56 respondents. The research instrument used a questionnaire. Bivariate analysis used the chi-square test with a significance level of 95%. Statistical tests show that there is a significant relationship between knowledge (p value=0.003) and attitude (p-value=0,029) with measures to prevent TB transmission. It can be concluded that there is a relationship between knowledge and attitudes with measures to prevent pulmonary TB transmissions. It is hoped that nursing staff at community health centers can be more optimal in disseminating information to the public, especially pulmonary sufferers and families, so they can increase understanding of the appropriate actions in preventing transmission of pulmonary TB to the other people.Keywords: Attitude, Knowledge, measures to prevent transmission, pulmonary tuberculosis